EXAMINATION OF CLASSROOM TEACHING PROGRAM CONTENT IN TURKEY IN TERMS OF TECHNO-PEDAGOGICAL COMPETENCIES - Barış YAMAN (Fırat University, 2019)
In this study, classroom teaching program content for the Faculty of Education in Turkey was aimed to investigate in terms of techno-pedagogical competencies. For this purpose, the content of Inonu University Faculty of Education classroom teaching program was examined. In this study, document analysis method was used. Collected data was analyzed by content analysis method. According to this; it was concluded that the number of courses, content and credits given in the teaching of techno-pedagogical competencies in the classroom teaching program was insufficient, and that the number of techno-pedagogical courses, content and credits should be increased in the first quarter of 2000s in relation to the technology used for instructional purposes.